2009
DOI: 10.2215/cjn.03410708
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Validation of Aortic Calcification Measurement from Lateral Bone Densitometry in Dialysis Patients

Abstract: Background and objectives: Vascular calcification (VC) contributes to increased cardiovascular (CV) disease in dialysis patientsand is inversely correlated with bone mineral density (BMD). Screening for VC may determine patients at greater CV risk and bone densitometry may have dual role in assessing VC as well as BMD. The aim of this study was to determine measurement of VC using dual-energy x-ray absorptiometry (DXA) with correlation to gold standard computed tomography (CT).Design, setting, participants, & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…0.0001) using lateral DXA (13). This simplified 8-point score may provide a quick, accurate tool for assessment of AAC, consistent with other studies that have shown good correlation between the 2 methods (0.95) (8) and good reproducibility of the 8-point score (2,16,17).…”
Section: Discussionsupporting
confidence: 85%
“…0.0001) using lateral DXA (13). This simplified 8-point score may provide a quick, accurate tool for assessment of AAC, consistent with other studies that have shown good correlation between the 2 methods (0.95) (8) and good reproducibility of the 8-point score (2,16,17).…”
Section: Discussionsupporting
confidence: 85%
“…Regarding agreement with other imaging modalities for aortic calcification, DXA-based AAC24 scores have good-very good agreement with radiography 34, 35 and moderate-good agreement with CT 36, 37 . The two studies comparing DXA-based AAC24 scores and standard radiographs were large studies with experienced investigators and reported ICC of between 0.80-0.82 34, 35 , however the studies comparing DXA-based AAC24 scores with CT were considerable smaller (n=40-100), and only one study reported an ICC of 0.93 37 while the other study 36 used Spearman rank correlation (r s =0.58, P<0.0001) which does not measure agreement between tests 38 .…”
Section: Discussionmentioning
confidence: 94%
“…The two studies comparing DXA-based AAC24 scores and standard radiographs were large studies with experienced investigators and reported ICC of between 0.80-0.82 34, 35 , however the studies comparing DXA-based AAC24 scores with CT were considerable smaller (n=40-100), and only one study reported an ICC of 0.93 37 while the other study 36 used Spearman rank correlation (r s =0.58, P<0.0001) which does not measure agreement between tests 38 . Therefore the evidence for the agreement between AAC by DXA-based techniques with CT remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…DXA is limited by the presence of aortic calcifications, that are common in dialysis patients and that may lead to an overestimation of spine aBMD and T-score. 22 This could explain the lack of difference in spine T-score in HD and PD patients compared with controls, whereas their hip T-score was lower. DXA has other technical limitations.…”
Section: Discussionmentioning
confidence: 99%